Talking to James Baldwin: Alain Mabanckou’s Jimmy - Schwarz, Bill (Études littéraires africaines, 2017)
« Talking to James Baldwin » explores the consequences of the intimacy which many readers experience when they read Baldwin’s prose. What are we to do when we confront this intimacy ? What ethical questions does this raise ? What is there in Baldwin’s writings which enables us to imagine productively the relations between the dead and the living ?